Интеллектуализация систем управления производством - Тимашова, Л. А.; Лещенко, В. А.; Морозова, А. И.; Таран, Л. Ю. (НТУ "ХПИ", 2017)
Представлены результаты интеллектуализации системы управления производством с помощью работающих со знаниями технологий. Приведено онтологическое описание системы управления и задач, связанных с представлением изделия, контроля обеспеченности производственной программы технической документацией и контроля структуры документов.

The results of the intellectualization of the production management system with the help of knowledgeable technologies are presented. An ontological description of the management system and tasks associated with the presentation of the product, control of the provision of the production program with technical documentation and control of the structure of documents is given.
Intellectualization of management systems
Keywords: изделие; производственная программа; структура документов; знания; система управления цехом; ТД; условия цеха; УЦ; production; management tasks; product; production program